2010
DOI: 10.2165/11319170-000000000-00000
|View full text |Cite
|
Sign up to set email alerts
|

Improving Adverse Drug Reaction Reporting in Hospitals

Abstract: This study shows that regular visits by a CRA increases the number of ADRs collected by a Regional Pharmacovigilance Centre. Another interesting consequence was the rise in spontaneous reporting by healthcare professionals following the set-up of this system. Further assessment of this procedure is necessary for the long-term evaluation of its effectiveness.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(10 citation statements)
references
References 21 publications
2
8
0
Order By: Relevance
“…Another intervention, based on educational presentations and monthly reminders, resulted in an increase in spontaneous ADR reporting in hospital settings [22]. Educational sessions plus regular visits by a research assistant increased both the number of ADRs recorded and the number of reporters [23]. The effect achieved by our educational intervention was similar to that obtained by other controlled studies that included physicians in the intervention group [21,22,24].…”
Section: Comparison Between Our Study and Others Aimed At Improving Asupporting
confidence: 75%
See 1 more Smart Citation
“…Another intervention, based on educational presentations and monthly reminders, resulted in an increase in spontaneous ADR reporting in hospital settings [22]. Educational sessions plus regular visits by a research assistant increased both the number of ADRs recorded and the number of reporters [23]. The effect achieved by our educational intervention was similar to that obtained by other controlled studies that included physicians in the intervention group [21,22,24].…”
Section: Comparison Between Our Study and Others Aimed At Improving Asupporting
confidence: 75%
“…The follow-up period was short if compared to those used in other published educational interventions in pharmacovigilance [21][22][23]. Owing to the termination of the collaboration agreement between the two bodies involved (the university and ADR adverse drug reaction, CI confidence interval, RR relative risk *RR for the two 4-month intervals is the adjusted RR of ADR reporting between the pre-intervention period and the two 4-month intervals of the post-intervention period in the control group.…”
Section: Effect Durationmentioning
confidence: 99%
“…HCPs should consider ADR reporting as an obligation [29], especially in view of their potential impact on outcomes and costs, which can be appreciably reduced with improved medicine management [3][4][5]. At Sebokeng Hospital, 98% of HCPs now indicated that it was necessary to report ADRs, similar to the findings from a tertiary hospital in India (97%) [30].…”
Section: Discussionmentioning
confidence: 91%
“…4 In the USA, ADEs account for nearly 100 000 emergency hospitalisations each year in this age group. 5 Different approaches exist for estimating medication harm resulting in hospitalisation, such as medical record reviews, [6][7][8][9][10][11][12] analysis of spontaneous reporting data, [13][14][15][16][17][18][19] and identification of ADE-related codes from the International Classification of Diseases (ICD) on inpatient records. [20][21][22][23][24][25][26] Some of these methods are labour-intensive, whereas others are subject to under-reporting and selection bias.…”
Section: Introductionmentioning
confidence: 99%